2022
DOI: 10.3928/19382359-20211209-03
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents and Young Adults with Cancer: Survivorship and Special Considerations

Abstract: Adolescents and young adults (AYAs) who have cancer face a distinct set of challenges beginning during the initial diagnosis, extending throughout treatment, and continuing into survivorship. Owing to significant strides made in cancer therapy in recent decades, more than 80% of this group will go on to become long-term survivors. Despite these improvements, however, many AYAs continue to have poorer outcomes when compared with older and younger patients. The purpose of this article is to underscore the unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…AYAs are recognized to be a unique and complex population, reporting higher rates of distress and lower QOL than older adults with cancer ( 125 ). For example, a recent study reported that AYA cancer survivors report more anxiety (15.1% vs. 6.6%) and mood disorders (14.8% vs. 8.9%) than older adults ( 126 ).…”
Section: Discussionmentioning
confidence: 99%
“…AYAs are recognized to be a unique and complex population, reporting higher rates of distress and lower QOL than older adults with cancer ( 125 ). For example, a recent study reported that AYA cancer survivors report more anxiety (15.1% vs. 6.6%) and mood disorders (14.8% vs. 8.9%) than older adults ( 126 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, radiotherapy remains integral in the cure of many childhood cancers, and although childhood cancer is rare, adult CCS are a growing, medically complex population [ 6 ]. Survivorship programs dedicated to caring for CCS provide individualized, guideline-based care plans to ensure that CCS receive critical surveillance as they age from childhood into adolescence and adulthood [ 9 •].…”
Section: Special Considerations For Ccsmentioning
confidence: 99%